DEVELOPMENT OF A MATHEMATICAL MODEL FOR DETERMINING THERMAL INDICATORS OF A BLAST MELTING FACTOR AT ANY POINT OF THE LAYER - Hlushchenko, O.L.; Kuvaev, V. (SWorld-Ger Conference proceedings, 2024)
The work is devoted to the development of a mathematical model for determining the thermal parameters of blast furnace smelting. The ability to determine these parameters at any point in the layer will allow us to take into account the peculiarities of he